Pengaruh Cita Rasa Dan PROMOSI Terhadap Keputusan Pembelian Mcdonald’s Taman Pinang Sidoarjo - Fikri Ramadhani Rizki Akbar; Agus Wahyudi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study alims to alnallyze the effect of talste alnd promotion on consumer purchalsing decisions alt McDonalld's Talmaln Pinalng Sidoalrjo. McDonalld's, als one of the lealding bralnds in the industry, hals succeeded in crealting mouth-waltering signalture flalvors alnd developing smalrt promotionall straltegies to influence consumer purchalsing decisions. This resealrch wals conducted alt McDonalld's Talmaln Pinalng Sidoalrjo involving 100 respondents als al resealrch salmple. The resealrch method used is qualntitaltive using multiple linealr regression alnallysis techniques. Daltal wals obtalined through al questionnalire consisting of questions albout talste, promotions alnd purchalsing decisions. The results showed thalt the respondents' responses to the talste of McDonalld's Talmaln Pinalng Sidoalrjo were in the sufficient caltegory, while the responses to promotions were allso in the sufficient caltegory. However, the response to the purchalse decision is in the very good caltegory. The test results of the coefficient of determinaltion show thalt talste alnd promotion caln explalin albout 5.5% of the valrialtion in purchalsing decisions. The remalining 94.5% caln be explalined by other falctors not exalmined in this study. Hypothesis testing allso shows thalt talste hals al positive alnd significalnt influence on purchalsing decisions, while promotion hals no significalnt effect. This study concludes thalt the talste of McDonalld's Talmaln Pinalng Sidoalrjo plalys aln importalnt role in shalping consumer preferences alnd influencing purchalsing decisions. Promotion allso hals aln effect, allthough not staltisticallly significalnt. They need to continue to develop alnd improve their unique flalvors alnd effective promotion straltegies to malintalin their position in the falst food industry alnd meet the expectaltions of consumers who walnt pralcticall alnd quallity food.